برنامج تدريبي لإكساب طلبة المرحلة الإعدادية مهارات الخطابة والالقاء - عودة، إخلاص هاشم (جامعة القادسية - كلية الآداب, 2019)
أدى انتشار التكنولوجيا وتطورها إلى تغير في المجتمعات من جميع النواحي، ومنها النواحي التربوية. وبما أن العملية التعليمية هي الصورة التي تعكس فلسفة التربية في أي مجتمع، فكان لزاما على المعلم استخدام أحدث الطرائق والوسائل الحديثة لتطوير العملية التعليمة ليواكب التغير الحادث في المجتمعات، فأهمية التربية تكمن في درجة وعي التدريسي بعملية تطبيق مكوناته. وبذلك عملت الباحثة على دراسة (برنامج تدريبي لإكساب طلبة المرحلة الإعدادية مهارات الخطابة والإلقاء)، فتكون البحث من الفصل الأول والذي تضمن مشكلة البحث حيث وجدت الباحثة مجموعة من المشكلات التي يعانيها الطلبة في ممارسة الخطابة والإلقاء. إذ أن التربية تعتمد على مفردات (محدودة) في مادة التربية الفنية. كما تضمن الفصل الأول الأهمية والأهداف والحدود وتعريف للمصطلحات أما الفصل الثاني فتضمن (دور تكنولوجيا التعليم في تطوير عملية التدريس) و (الخطابة- قيمتها- أغراضها- أنواعها) و (مهارات الإلقاء)، بينما الفصل الثالث تضمن منهجية البحث وإجراءاته، أما الفصل الرابع فتضمن النتائج والاستنتاجات والتوصيات والمقترحات، ومن ثم المصادر والمراجع.
The spread and evolution of technology have led to changes in societies in all respects, including educational aspects. Since the educational process is the image that reflects the philosophy of education in any society, the teacher was required to use the latest methods and modern methods to develop the educational process to keep pace with the change in the communities, The importance of education lies in the degree of educational awareness of the process of applying its components. Thus, the researcher worked on a study (training program for students of junior high school). The research consists of the first chapter, which included the problem of research, where the researcher found a set of problems that students experience in the practice of public speaking and dropping. As the education depends on the vocabulary (limited) in the art education. as included in the first chapter The importance, objectives, limits and definition of terms. The second chapter includes (the role of educational technology in the development of teaching process) and (rhetoric- value- purposes- types) and (skills shed), while the third chapter included the methodology and procedures of research, either Chapter IV contains the findings, conclusions, recommendations and proposals, and then sources and references.
Keywords: طلبة المرحلة الإعدادية -- البرامج التدريبية -- الأدب العربي -- الخطابة العربية